Firm-level factors influencing CEO turnover in Saudi Arabia - Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Business & Management, 2024)
Saudi Arabian firms are evolving from government or family-run businesses to larger corporations due to foreign investments. However, the role of a chief executive officer (CEO) is retained by family members. This study investigates the factors responsible for CEO turnover in Saudi Arabia in relationship to firm performance and compares them against those in other countries. This study is the first to look at CEO turnover in the Saudi context. Using panel data from 169 Saudi firms listed between 2007 and 2014, average marginal effects from a binary probit model, and differences-in-differences analysis, the effects of the following independent variables were assessed: CEO age, retirement age, tenure, pay, shareholdings, duality, board size and composition, firm ownership, and firm performance, with CEO turnover as the binary dependent variable. Results indicated that CEO turnover negatively relates to firm performance, irrespective of whether the dismissal is voluntary or forced, reaffirming a negative turnover—performance sensitivity. Further, CEOs with less than 5% shareholding face a greater likelihood of dismissal by the board, whereas larger shareholders are more entrenched. CEOs in government-owned firms show higher performance-related turnover, while those in family or foreign firms show no such relationship.
Keywords: G32; G34; G38; M12; O16; 650; CEO turnover; corporate governance; firm performance; forced dismissal; Saudi Arabia; voluntary dismissal